Spinel type composite oxide catalyst and preparation method thereof

By using spinel-type composite oxide catalysts in the catalyst and combining with specific process treatments, the existing catalysts have been solved, and the performance and service life of the catalysts have been significantly improved.

CN119565644AActive Publication Date: 2025-03-07山东东岳绿冷科技有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510112782.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-03-07
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing catalysts have problems of low selectivity, insufficient activity and poor stability in the industrial production of 3,3,3-trifluoropropylene, which affects the yield and purity of the product.

Method used

The spinel-type composite oxide catalyst is used to optimize the catalyst surface structure and active sites through adjustable A and B ion types and proportions. Combined with the citric acid-assisted sol-gel method and specific pretreatment, calcination and fluorination treatment processes, the stability, catalytic activity and selectivity of the catalyst are significantly improved.

Benefits of technology

It significantly improves the stability and catalytic activity of the catalyst, enhances the selectivity and resistance to carbon deposits, and extends the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of fluorine chemical industry, and particularly relates to a spinel type composite oxide catalyst and a preparation method thereof. The general formula of the catalyst is AB2O4, and the preparation method of the catalyst comprises the following steps: (1) mixing and dissolving raw materials on a site A and a site B in deionized water, adding citric acid monohydrate, and mixing and stirring to obtain sol; (2) evaporating the sol to dryness to obtain dry glue, then drying the dry glue, then pretreating the dried dry glue, and roasting after pretreatment to obtain a spinel type composite oxide catalyst; and (3) putting the spinel type composite oxide catalyst into a fixed bed reactor, and simultaneously introducing N2 and HF to carry out fluorination treatment. The surface structure and active sites of the catalyst are optimized by utilizing adjustable A-site and B-site ion types and proportions, and the stability, catalytic activity and selectivity of the catalyst are remarkably improved by combining a citric acid-assisted sol-gel method and specific pretreatment, roasting and fluorination treatment processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fluorine chemical industry, and specifically relates to a spinel type composite oxide catalyst and a preparation method thereof. Background Art

[0002] 3,3,3-Trifluoropropene (TFP) is an important compound with excellent properties such as low global warming potential (GWP), high energy efficiency and low toxicity, so it has received extensive attention and research. This compound is widely used in refrigerants, foaming agents, solvents and polymerization monomers. Especially in the refrigeration industry, it is regarded as one of the ideal candidate materials to replace the high GWP refrigerant 1,1,1,2-tetrafluoroethane (HFC-134a). However, in its industrial production process, the selectivity and activity of the catalyst directly affect the quality and cost of the product. Therefore, the development of an efficient and stable catalyst is of great significance for the industrial production of 3,3,3-trifluoropropene. 1,1,3-Trichloropropene (TCP) is a key raw material for the synthesis of 3,3,3-trifluoropropene. Under the action of a catalyst, TCP reacts with hydrofluoric acid (HF) in a gas phase fluorination reaction, which is a new method for preparing 3,3,3-trifluoropropene. The key to this reaction lies in the selection of the catalyst, because the activity, selectivity and stability of the catalyst will directly affect the yield and purity of the product. At present, the existing catalyst systems mainly include Cr-based catalysts, Al-based catalysts and other composite oxide catalysts. However, these catalysts have exposed some problems in practical applications, such as easy catalyst deactivation, low selectivity, low conversion rate and complex post-processing. Therefore, developing a new catalyst to improve the conversion rate and selectivity of the reaction and optimize the stability of the catalyst has become a hot topic in current research. Summary of the invention

[0003] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a spinel-type composite oxide catalyst, which optimizes the surface structure and active sites of the catalyst by utilizing adjustable A and B site ion types and ratios, and combines a citric acid-assisted sol-gel method and specific pretreatment, calcination and fluorination treatment processes to significantly improve the stability, catalytic activity and selectivity of the catalyst.

[0004] Another object of the present invention is to provide a method for preparing a spinel-type composite oxide catalyst, which has a simple process and is easy to mass produce.

[0005] The technical solution adopted by the present invention is as follows: The preparation method of the spinel-type composite oxide catalyst, the general formula of the spinel-type composite oxide catalyst is AB2O4, wherein A is one of Mg, Zn or Ni, and B is Al or Cr; The method for preparing the spinel-type composite oxide catalyst comprises the following steps: (1) Mixing the raw materials at the A position and the B position and dissolving them in deionized water, adding monohydrated citric acid, mixing and stirring to obtain a sol; (2) evaporating the sol to dryness to obtain a dry glue, then drying the dry glue, and then pre-treating the dried dry glue. After the pre-treatment, calcining the dry glue at 500-800° C. to obtain a spinel-type composite oxide catalyst; (3) The spinel composite oxide catalyst is placed in a fixed bed reactor and N2 and HF are introduced simultaneously for fluorination treatment. The steps of the fluorination treatment are: first, fluorination at 200-400°C for 12-48 hours, and then the temperature is increased to 450-650°C and the fluorination is continued for 36-60 hours.

[0006] The raw material at the A position is one of MgCl2·6H2O, Zn(NO3)2·6H2O or Ni(NO3)2·6H2O; the raw material at the B position is Al(NO3)3·9H2O or CrCl3·6H2O.

[0007] The molar ratio of the raw materials at the A position to the raw materials at the B position is 1:(1-4); the mass ratio of the added amount of citric acid monohydrate to the total amount of the raw materials at the A position and the B position is (0.9-1.5):1.

[0008] In the step (1), the mixing and stirring is performed at room temperature for 1-2 hours.

[0009] In the step (2), the evaporation temperature is 60-90°C; the drying temperature is 90-110°C.

[0010] In the step (2), the pretreatment temperature is 180-220°C and the time is 30-60 minutes.

[0011] In the step (2), the calcination temperature is 500-800°C and the calcination time is 4-6 hours.

[0012] In the step (3), the flow rate of N2 is 0.5-4 L / min, and the flow rate of HF is 10-30 g / h.

[0013] The spinel-type composite oxide catalyst is prepared by the above-mentioned method for preparing the spinel-type composite oxide catalyst.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention prepares a high-performance spinel-type composite oxide catalyst by replacing the A and B positions of the spinel with different elements. Since the ions at the A and B positions can directly participate in the catalytic reaction as active components, the catalyst has high catalytic activity and selectivity; at the same time, when they form the spinel composite oxide, the number of oxygen vacancies on the catalyst surface increases, thereby significantly enhancing the catalyst's ability to resist carbon deposition and effectively extending the catalyst's service life. DETAILED DESCRIPTION

[0015] The present invention is further described below with reference to the embodiments, but they do not limit the implementation of the present invention.

[0016] The raw materials used in the examples and comparative examples are conventional commercially available raw materials unless otherwise specified, and the process methods used in the examples and comparative examples are conventional methods in the art unless otherwise specified.

[0017] Example 1 The general formula of the spinel-type composite oxide catalyst is MgAl2O4, and the preparation method thereof comprises the following steps: (1) Weigh 20.3 g of MgCl2·6H2O and 75 g of Al(NO3)3·9H2O and dissolve them in deionized water, then add 100 g of citric acid monohydrate, mix and stir at room temperature for 2 h to fully dissolve and complex, and obtain a sol; (2) The sol was transferred to a 60°C water bath and evaporated to obtain a compact dry glue, and then the dry glue was transferred to a 90°C oven for overnight drying to allow it to expand completely. The dried dry glue was then transferred to a muffle furnace for pretreatment at a temperature of 180°C for 60 min. The pretreated dry glue was then transferred to a muffle furnace at 500°C for calcination for 6 h to obtain a spinel-type composite oxide catalyst. (3) 50 mL of the spinel composite oxide catalyst was loaded into a fixed bed reactor, and N2 and HF were introduced simultaneously for fluorination treatment, wherein the flow rate of N2 was 0.5 L / min, and the flow rate of HF was 10 g / h. The steps of the fluorination treatment were: first, fluorination was performed at 200°C for 48 h, then the temperature was raised to 450°C and the fluorination was continued for 60 h, and then the catalyst was set aside for use after fluorination.

[0018] Example 2 The general formula of the spinel-type composite oxide catalyst is MgCr2O4, and the preparation method thereof comprises the following steps: (1) Weigh 20.3 g of MgCl2·6H2O and 53.2 g of CrCl3·6H2O and dissolve them in deionized water, then add 100 g of citric acid monohydrate, mix and stir at room temperature for 1.8 h to fully dissolve and complex, and obtain a sol; (2) The sol was transferred to a 70°C water bath for evaporation to obtain a compact dry gel, and then the dry gel was transferred to a 95°C oven for overnight drying to allow it to expand completely. The dried dry gel was then transferred to a muffle furnace for pretreatment at a temperature of 190°C for 55 min. The pretreated dry gel was then transferred to a muffle furnace for calcination at 550°C for 5.5 h to obtain a spinel-type composite oxide catalyst. (3) 50 mL of the spinel composite oxide catalyst was loaded into a fixed bed reactor, and N2 and HF were introduced simultaneously for fluorination treatment, wherein the flow rate of N2 was 1 L / min, and the flow rate of HF was 15 g / h. The steps of the fluorination treatment were: first, fluorination was carried out at 250°C for 36 h, then the temperature was raised to 500°C and fluorination was continued for 54 h, and then the catalyst was set aside for use after fluorination.

[0019] Example 3 The general formula of the spinel-type composite oxide catalyst is ZnAl2O4, and the preparation method thereof comprises the following steps: (1) Weigh 29.7 g of Zn(NO3)2·6H2O and 75 g of Al(NO3)3·9H2O and dissolve them in deionized water. Then add 100 g of citric acid monohydrate and stir at room temperature for 1.5 h to fully dissolve and complex to obtain a sol. (2) The sol was transferred to a 75°C water bath for evaporation to obtain a compact dry gel, and then the dry gel was transferred to a 100°C oven for overnight drying to allow it to expand completely. The dried dry gel was then transferred to a muffle furnace for pretreatment at a temperature of 200°C for 50 min. The pretreated dry gel was then transferred to a muffle furnace at 650°C for calcination for 5 h to obtain a spinel-type composite oxide catalyst. (3) 50 mL of the spinel composite oxide catalyst was loaded into a fixed bed reactor, and N2 and HF were introduced simultaneously for fluorination treatment, wherein the flow rate of N2 was 2 L / min, and the flow rate of HF was 20 g / h. The steps of the fluorination treatment were: first, fluorination was performed at 300°C for 24 h, then the temperature was raised to 550°C and fluorination was continued for 48 h, and then the catalyst was set aside for use after fluorination.

[0020] Example 4 The general formula of the spinel-type composite oxide catalyst is ZnCr2O4, and the preparation method thereof comprises the following steps: (1) Weigh 29.7 g of Zn(NO3)2·6H2O and 53.2 g of CrCl3·6H2O and dissolve them in deionized water, then add 100 g of citric acid monohydrate, mix and stir at room temperature for 1.2 h to fully dissolve and complex, and obtain a sol; (2) The sol was transferred to an 80°C water bath for evaporation to obtain a compact dry gel, and then the dry gel was transferred to a 105°C oven for overnight drying to allow it to expand completely. The dried dry gel was then transferred to a muffle furnace for pretreatment at a temperature of 210°C for 45 min. The pretreated dry gel was then transferred to a muffle furnace at 700°C for calcination for 4.8 h to obtain a spinel-type composite oxide catalyst. (3) 50 mL of the spinel composite oxide catalyst was loaded into a fixed bed reactor, and N2 and HF were introduced simultaneously for fluorination treatment, wherein the flow rate of N2 was 3 L / min, and the flow rate of HF was 22 g / h. The steps of the fluorination treatment were: first, fluorination was carried out at 350°C for 18 h, then the temperature was raised to 600°C and fluorination was continued for 42 h, and then the catalyst was set aside for use after fluorination.

[0021] Example 5 The general formula of the spinel-type composite oxide catalyst is NiAl2O4, and the preparation method thereof comprises the following steps: (1) Weigh 29.1 g of Ni(NO3)2·6H2O and 75 g of Al(NO3)3·9H2O and dissolve them in deionized water. Then add 100 g of citric acid monohydrate and stir at room temperature for 1 h to fully dissolve and complex to obtain a sol. (2) The sol was transferred to a water bath at 85°C and evaporated to dryness to obtain a compact dry glue, which was then transferred to an oven at 110°C and dried overnight to allow it to expand completely. The dried dry glue was then transferred to a muffle furnace for pretreatment at a temperature of 215°C for 40 min. The pretreated dry glue was then transferred to a muffle furnace at 750°C and calcined for 4.3 h to obtain a spinel-type composite oxide catalyst. (3) 50 mL of the spinel composite oxide catalyst was loaded into a fixed bed reactor, and N2 and HF were introduced simultaneously for fluorination treatment, wherein the flow rate of N2 was 3.5 L / min, and the flow rate of HF was 25 g / h. The steps of the fluorination treatment were: first, fluorination was carried out at 380°C for 15 h, then the temperature was raised to 630°C and fluorination was continued for 40 h, and then the catalyst was set aside for use after fluorination.

[0022] Example 6 The general formula of the spinel-type composite oxide catalyst is NiCr2O4, and the preparation method thereof comprises the following steps: (1) Weigh 29.1 g of Ni(NO3)2·6H2O and 53.2 g of CrCl3·6H2O and dissolve them in deionized water, then add 100 g of citric acid monohydrate, mix and stir at room temperature for 1.1 h to fully dissolve and complex, and obtain a sol; (2) The sol was transferred to a 90°C water bath for evaporation to obtain a compact dry glue, and then the dry glue was transferred to a 108°C oven for overnight drying to allow it to expand completely. The dried dry glue was then transferred to a muffle furnace for pretreatment at a temperature of 220°C for 35 min. The pretreated dry glue was then transferred to a muffle furnace at 800°C for calcination for 4 h to obtain a spinel-type composite oxide catalyst. (3) 50 mL of the spinel composite oxide catalyst was loaded into a fixed bed reactor, and N2 and HF were introduced simultaneously for fluorination treatment, wherein the flow rate of N2 was 4 L / min, and the flow rate of HF was 28 g / h. The steps of the fluorination treatment were: first, fluorination was performed at 400°C for 12 h, and then the temperature was raised to 650°C and fluorination was continued for 36 h. After fluorination, it was ready for use.

[0023] Comparative Example 1 The difference from Example 2 is that in step (2), the calcination temperature is 950° C., and the rest is the same as Example 2.

[0024] Comparative Example 2 The difference from Example 2 is that MgCl2·6H2O in step (1) is replaced by 12.6 g of FeCl2·4H2O, and the rest is the same as Example 2.

[0025] Comparative Example 3 The difference from Example 2 is that in step (3), the fluorination treatment step is: first fluorination at 250°C for 36 hours, then heating to 800°C and continuing fluorination for 54 hours, and the rest is the same as Example 2.

[0026] 50 mL of each of the fluorinated catalysts prepared in Examples 1-6 and Comparative Examples 1-3 were loaded into a fixed bed reactor, TCP and HF were introduced, the reaction temperatures were set to 300°C and 350°C, respectively, the molar ratio of HF to TCP was controlled to be 10:1, and the space velocity was 250 h -1 , to obtain TFP.

[0027] The TCP conversion (%) and TFP selectivity (%) of each reaction were calculated respectively.

[0028] The test results are shown in Table 1.

[0029] Table 1 Performance test results

[0030] It can be seen from the test data in Table 1 that the catalysts prepared in Examples 1-6 exhibit different catalytic properties due to the different elements used, calcination temperatures and other conditions, among which the catalyst prepared from the two elements Mg and Cr in Example 2 has the best catalytic effect.

[0031] Compared with Example 2, in Comparative Example 1, the specific surface area of ​​the catalyst dropped sharply due to the increase in calcination temperature, so the activity and selectivity of the catalyst decreased.

[0032] Compared with Example 2, the catalyst activity in Comparative Example 2 decreased due to the replacement of raw material Mg with Fe, which means that the presence of Mg is more beneficial to the activity of the catalyst. Since Mg is an alkaline earth metal element, the catalyst has more alkaline centers and thus has a stronger ability to resist carbon deposition.

[0033] Compared with Example 2, in Comparative Example 3, the catalyst was over-fluorinated due to the increase in the fluorination temperature of the catalyst, resulting in a decrease in the activity of the catalyst.

Claims

1. A method for preparing a spinel-type composite oxide catalyst, characterized in that: The general formula of the spinel-type composite oxide catalyst is AB2O4, wherein A is one of Mg, Zn or Ni, and B is Al or Cr; The method for preparing the spinel-type composite oxide catalyst comprises the following steps: (1) Mix the raw materials at the A position and the raw materials at the B position and dissolve them in deionized water, add monohydrated citric acid, mix and stir to obtain a sol; (2) evaporating the sol to dryness to obtain a dry glue, then drying the dry glue, and then pre-treating the dried dry glue. After the pre-treatment, calcining the dry glue at 500-800° C. to obtain a spinel-type composite oxide catalyst; (3) The spinel composite oxide catalyst is placed in a fixed bed reactor and N2 and HF are introduced simultaneously for fluorination treatment. The steps of the fluorination treatment are: first, fluorination at 200-400°C for 12-48 hours, and then the temperature is increased to 450-650°C and the fluorination is continued for 36-60 hours.

2. The method for preparing the spinel-type composite oxide catalyst according to claim 1, characterized in that: The raw material at the A position is one of MgCl2·6H2O, Zn(NO3)2·6H2O or Ni(NO3)2·6H2O; the raw material at the B position is Al(NO3)3·9H2O or CrCl3·6H2O.

3. The method for preparing the spinel-type composite oxide catalyst according to claim 1, characterized in that: The molar ratio of the raw materials at the A position to the raw materials at the B position is 1:(1-4); the mass ratio of the added amount of citric acid monohydrate to the total amount of the raw materials at the A position and the B position is (0.9-1.5):

1.

4. The method for preparing the spinel-type composite oxide catalyst according to claim 1, characterized in that: In the step (1), the mixing and stirring is performed at room temperature for 1-2 hours.

5. The method for preparing the spinel-type composite oxide catalyst according to claim 1, characterized in that: In the step (2), the evaporation temperature is 60-90°C; the drying temperature is 90-110°C.

6. The method for preparing the spinel-type composite oxide catalyst according to claim 1, characterized in that: In the step (2), the pretreatment temperature is 180-220°C and the time is 30-60 minutes.

7. The method for preparing a spinel-type composite oxide catalyst according to claim 1, characterized in that: In the step (2), the calcination time is 4-6 hours.

8. The method for preparing a spinel-type composite oxide catalyst according to claim 1, characterized in that: In the step (3), the flow rate of N2 is 0.5-4 L / min.

9. The method for preparing a spinel-type composite oxide catalyst according to claim 1, characterized in that: In the step (3), the flow rate of HF is 10-30 g / h.

10. A spinel-type composite oxide catalyst, characterized in that: The catalyst is prepared by the method for preparing the spinel-type composite oxide catalyst according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Catalyst for fluoridation and preparation method for same

    CN103041819A

  • Preparation method of spinel type catalyst for preparing vinyl chloride by ethane oxychlorination

    CN110479298A

  • Florination catalyst, its manufacturing method and use

    CN1651137A

  • Process for the preparation of 1,1,1,3,3-pentafluoropropane and 1,1,1,3,3,3-hexafluoropropane

    US20070123742A1